2021
DOI: 10.3389/fimmu.2021.774601
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium of Human Amniotic Epithelial Cells Alleviates Experimental Allergic Conjunctivitis Mainly by IL-1ra and IL-10

Abstract: Allergic conjunctivitis (AC) is the most prevalent form of mucosal allergy, and the conditioned medium (CM) from mesenchymal stem cells has been reported to attenuate some allergic diseases. However, the therapeutic effects of CM from different tissue stem cells (TSC-CM) on allergic diseases have not been tested. Here, we studied the effects of topical administration of different human TSC-CM on experimental AC (EAC) mice. Only human amniotic epithelial cell-CM (AECM) significantly attenuated allergic eye symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Additional characteristics are its ability to inhibit IgE release by effector B cells and mast cell activation and function, as well as exhibit an antihistamine effect. As such, data thus far supports continued research in this area as a potential, novel treatment for AC [ 203 ].…”
Section: Potential Therapeutic Targetsmentioning
confidence: 76%
See 1 more Smart Citation
“…Additional characteristics are its ability to inhibit IgE release by effector B cells and mast cell activation and function, as well as exhibit an antihistamine effect. As such, data thus far supports continued research in this area as a potential, novel treatment for AC [ 203 ].…”
Section: Potential Therapeutic Targetsmentioning
confidence: 76%
“…Wu et al hypothesized that there is a potential benefit from tissue stem cell conditioned medium (CM) on AC. In a study comparing various types of topically applied tissue stem cell CM, it was the human amniotic epithelial cell CM that demonstrated a significant reduction in the signs and symptoms of AC [ 203 ]. The utility in using tissue stem cells in general is their ability to self-renew and differentiate, thus allowing the repair of various types of damage.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…Notably, treatment with CM secreted by AECs increased the levels of anti-inflammatory factors TGF-β and IL-10 as well as the expression of Foxp3, a protein involved in immune system responses. 28 A study showed that soluble factors contained in AM-CM significantly reduced the inflammatory response on human limbal myofibroblast by inhibiting NF-κB activity and subsequently abrogating the synthesis and secretion of proinflammatory chemokines CCL2, CCL5, and CXCL10. 29 Another report has shown that the addition of rat AECs-CM to lipopolysaccharide-activated macrophages evoked anti-inflammatory effects via a decrease in TNF-α expression and inhibited tumor cell proliferation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In some preclinical studies, Oksana et al found that the secretome derived from MSCs reduces disease severity in inflammatory arthritis mice, enhances Treg function, and restores the ratio of Treg cells and Th17 cells [ 33 ]. Our recent study has demonstrated that the conditioned medium or the secretome derived from human amniotic epithelial cells (AEC-SC) attenuates experimental allergic conjunctivitis in mice [ 34 ]. However, the protective effect of secretome or paracrine factor derived from stem cells on psoriasis has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%